The Integral Assessment of Playing Tactics in National Football Teams - Viktor Kostiukevych; Oksana Shynkaruk; Olha Borysova; Valentina Voronova; Tetiana Vozniuk; Eduard Doroshenko; Ruslana Sushko; Iryna Kulchytska (OVS LLC, 2024)
Objectives. The objective of the study was to determine the features of competitive activities among national football teams based on the integral assessment of playing tactics. Materials and methods. The study was conducted during the 2024 European Football Championship. The competitive activities of national football teams from European countries (Germany, Spain, England, Switzerland, France, Portugal, Netherlands, Turkey) were analyzed, focusing on the playing tactics in 50 halves. In order to carry out the study, the following methods were used: theoretical analysis of literature sources; pedagogical observation of competitive activities; analysis of video materials of competitive activities; methods of mathematical statistics. The statistical analysis of the research results was conducted using descriptive mathematical statistics. The sample was characterized by determining the arithmetic mean, standard deviation (S), and coefficient of variation (V). The significance of observed differences in the indicators was assessed using the parametric Student's t-test for independent samples. Prior to this, the data's conformity to a normal distribution was verified using the Shapiro-Wilk W-test. Results. A methodology for the integral assessment of the tactics undertaken by national football teams was developed. The integral assessment of team tactics consisted of 10 specific coefficients that reflect the main components of football players' competitive activities in the phases of ball possession and recovery. The competitive activities in 50 halves of the 2024 European Football Championship were analyzed. The average value of the integral assessment of the tactics in national football teams was determined to be 5.62 ± 0.43 points. The findings revealed significant tactical variations between the teams, with Spain's use of high pressing and creative play contributing to their championship victory. A ten-point scale for evaluating the tactics of national football teams was developed, on the basis of which the level of competitive activities is interpreted. Conclusions. The developed methodology for monitoring and analyzing the tactics of football teams allows for targeted management influences on the competitive activities of football players at the operational, current, and stage levels.